Targeting the bHLH Transcriptional Networks by Mutated E Proteins in Experimental Glioma. (15th September 2014) - Beyeler, Sarah; Joly, Sandrine; Fries, Michel; Obermair, Franz-Josef; Burn, Felice; Mehmood, Rashid; Tabatabai, Ghazaleh; Raineteau, Olivier
Abstract: Glioblastomas (GB) are aggressive primary brain tumors. Helix-loop-helix (HLH, ID proteins) and basic HLH (bHLH, e.g., Olig2) proteins are transcription factors that regulate stem cell proliferation and differentiation throughout development and into adulthood. Their convergence on many oncogenic signaling pathways combined with the observation that their overexpression in GB correlates with poor clinical outcome identifies these transcription factors as promising therapeutic targets. Important dimerization partners of HLH/bHLH proteins are E proteins that are necessary for nuclear translocation and DNA binding. Here, we overexpressed a wild type or a dominant negative form of E47 (dnE47) that lacks its nuclear localization signal thus preventing nuclear translocation of bHLH proteins in long-term glioma cell lines and in glioma-initiating cell lines and analyzed the effects in vitro and in vivo. While overexpression of E47 was sufficient to induce apoptosis in absence of bHLH proteins, dnE47 was necessary to prevent nuclear translocation of Olig2 and to achieve similar proapoptotic responses. Transcriptional analyses revealed downregulation of the antiapoptotic gene BCL2L1 and the proproliferative gene CDC25A as underlying mechanisms. Overexpression of dnE47 in glioma-initiating cell lines with high HLH and bHLH protein levels reduced sphere formation capacities and expression levels of Nestin, BCL2L1, and CDC25A . Finally, the in vivo induction of dnE47 expression in established xenografts prolonged survival. In conclusion, our data introduce a novel approach to jointly neutralize HLH and bHLH transcriptional networks activities, and identify these transcription factors as potential targets in glioma. Stem Cells   2014;32:2583–2595